(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of work motivation and work discipline on job satisfaction. The research location was at Warung Pizarro. The sample used was 40 respondents. The data analysis technique used is Validity, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t-test and F-test. This shows that the better work motivation and work discipline, the better job satisfaction at Warung Pizarro. In the future, Warung Pizarro is expected to increase the amount of salary given to employees, give warnings or sanctions to employees who do not comply with applicable regulations at work and provide tasks according to the position and abilities of the employees.